Analysis of the PHWR benchmark transient using a high-order spherical harmonics-nodal collocation method and treatment of rod cusping effect. (May 2021) - Capilla, M.T.; Talavera, C.F.; Ginestar, D.; Verdú, G.
Abstract: We develop and validate node homogenization methods, based on one and three-dimensional node equivalent problems, that improve the volume weighted method for the treatment of the rod cusping effect. The numerical implementation of these techniques in a numerical approach based on general spherical harmonics, nodal collocation method, for arbitrary odd order L, and fully implicit time discretization, is verified on the AECL-7236 PHWR benchmark transient, showing the validity and convergence of the P 1 and P 3 approximations and the ability of the method to give accurate results for the relative power and scalar flux when a coarse spatial mesh combined with advanced homogenization techniques is used. Highlights: We develop node homogenization methods based on 1D and 3D node equivalent problems. Numerical implementation is based on spherical-harmonics nodal collocation method. The method is verified on the AECL-7236 PHWR benchmark for P1 and P3 approximations. Results show the accuracy for coarse spatial mesh and advance homogenization techniques.